Perancangan Model Bisnis Perubahan Swab Aja menjadi Klinik Menggunakan Metode Bisnis Model Kanvas - Nurmaryo Anggito; Ahmad Nurul Fajar (SAFE-Network, 2023)
This research is case study research at the Swab Aja. The aims of this research to find existing business model analysis Swab Aja; and to find a business model design for changing Swab Aja into a clinic using the Business Model Canvas. This research is qualitative research. The data used are primary data and secondary data. Secondary data was obtained through document analysis while primary data was obtained through field studies and interviews. Data collection techniques to be used in this research are: in-depth interviews); participant – observation); and Documentation. The interview guide used consisted of 50 questions. The interview guide was prepared based on the 9 stages of developing the canvas business model. The findings in this research are: there are changes in the components of key activities, value propositions, channels, and customer segments; the design of a new business model at the SWAB AJA Laboratory, namely changing its form to a clinic that provides various services besides SWAB and PCR tests such as physiotherapy, pharmacy, offline clinics and even delivery services; and a new brand is required for the SWAB AJA Laboratory so that the customer's image changes to increase sales.